The Effect of Social Support with Peer Leaders on Self-Management of Diarrhea in Infants/Toddlers with Diarrhea in Infants/Toddlers At Posyandu - Haryani, Sri; Yusniarita; Misniarti; Chandra Buana; Tri Widyastuti Handayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of social support with peer leaders on self-management of diarrhea in infants/toddlers among fellow diarrhea sufferers in infants/toddlers at the integrated health post in Rejang Lebong Regency. This research method uses a quantitative research type with a Quasi Experiment design in the intervention group and the control group. The results showed that in the Social Support and Self Management group before and after the intervention, Social Support and Self Management had an effect with a p value <0.000. In conclusion, social support and self management have a significant relationship after mothers read/get information from books and leaflets in caring for children with diarrhea at home. Keywords: Diarrhea, Social Support, Self Management